The Role of Women Farming Groups on Vegetable Agribusiness Income (A Case Study Women Farmers Group In Pala City, Dajan Peken Village, Tabanan District) - Putu Fajar Kartika Lestari; Amallia Ferhat (SEAS (Sustainable Environment Agricultural Science), 2023)
Vegetables are all types of plants that can be consumed or eaten either taken from the roots, stems, leaves, seeds, flowers, or other parts used to be processed into food. Vegetables are also one of the horticultural crop commodities that have an important role as a source of income for farmers' lives. This research was conducted at the KWT Pala City, Dajan Peken Village, Tabanan District, Tabanan Regency. The purpose of this study was to determine the income, level of farming efficiency, and contribution of KWT to family income in KWT Pala City, Dajan Peken Village, Tabanan District. The determination of respondents was carried out using the census method with a total of 20 respondents. The method in this research is income analysis and R/C Ratio. The results of this study indicate that the income of vegetable farming in the KWT of Pala City, during one production season, is IDR 22.016.900. The value of the R/C Ratio of vegetable farming in the KWT of Pala City is 2.18. It means the activities of vegetable farming in the place is worth to be developed because profitable in term of economy. Keywords: Vegetable farming, Women Farmer Group, Income, R/C Ratio